The isotopic patterns and source apportionment of nitrate and ammonium in atmospheric aerosol - Dong, Xinyuan; Guo, Qingjun; Han, Xiaokun; Wei, Rongfei; Tao, Zhenghua (The Science of the total environment, 2022)
Nitrate (NO3-) and ammonium (NH4+) are the major components in inorganic aerosol. However, their sources and formation processes remain unclear. This study conducted a year-round field measurement of TSP, PM2.5 and PM1.0 in five different sites in the Beijing-Tianjin-Hebei (BTH) region to determine the concentrations of water-soluble inorganic ions (WSIIs) and the isotopic compositions of inorganic nitrogen (δ15N-NH4+, δ15N-NO3-, and δ18O-NO3-). The results showed the highest concentration of WSIIs in winter and lowest in summer. δ15N-NO3-, δ18O-NO3-, and δ15N-NH4+ were in the range of -6.1–18.2, 52.2–103.8, and -28.7–36.2‰, respectively. The seasonal variations of δ15N-NO3- and δ15N-NH4+ were an indication of relative contributions of the main sources and effects of meteorological conditions. The source apportionment identified fossil fuel combustion (38.2–50.6%), agricultural emissions (18–24.7%), biomass burning (16.3–22.7%), and road dust/soil (8.7–23.4%) were the main sources of inorganic aerosols. The local sources and regional migration contributed to the level of inorganic aerosol pollution. In winter, the aerosol in the BTH region was affected by the air mass from the northwest. While in spring and summer, the air mass was mainly from the South China. The low temperature and high relative humidity favored to the formation of inorganic nitrogen aerosol, and solar radiation affected the formation processes of inorganic aerosols by changing the oxidation pathway of NO3- and accelerating the volatilization and dissociation of ammonium nitrate (NH4NO3). This study discovered the main source contributions of inorganic nitrogen aerosol using N and O isotopes composition, and the obtained information has a great importance in understanding the effects of meteorological conditions on formation and the contribution of regional transport. [Display omitted] •Isotopic patterns of inorganic nitrogen aerosol in the BTH region were reported.•Fossil fuel combustion accounted for 38.2– 50.6% of inorganic nitrogen aerosol.•Meteorological conditions played a vital role on formation processes.•The regional migration was from the northwest in winter, while south in summer.